Porphyrin based channel for separation of proton isotope: A density functional theory study. (December 2022) - Ayub, Amna; Gul, Sehrish; Ayub, Riffat; Bibi, Zeeshana; Hashmi, Muhammad Ali; Lakhani, Ahmed; Dahshan, A.; Ayub, Khurshid; Iqbal, Javed
Abstract: Porphyrin based 2D materials with single atom thickness and uniform pore size have not been explored for the proton isotopes separation. We computationally designed the porphyrin and its derivatives with the doping of oxygen, sulphur and selenium atoms and computed the kinetic energy barrier for H +, D +, and T + permeation through porphyrin and core modified porphyrins by using M05-2X along with 6-31G (d, p). Zero-point energy is calculated at transition state for H + and its other relevant isotopes permeation through porphyrin derivatives. Tunneling ratio of proton isotopes through these 2D structures is calculated by using zero-point energy (ZPE) difference of H + to its isotopes. Core modification of porphyrin provides better tunneling ratio for proton isotopes. Among these, mono selenium heteroporphyrin provides the most suitable results. Our study provides the molecular level insight of permeation pathway for proton isotopes through these 2D materials. Graphical abstract: Image 1 Highlights: We computationally designed the porphyrin and its derivatives with the doping of oxygen, sulphur and selenium atoms. Tunneling ratio of proton isotopes through these 2D structures is calculated by using zero-point energy (ZPE) difference of protium ion to its isotopes. Kinetic energy barrier for H+, D+, and T+ permeation through porphyrin and core modified porphyrins is computed.